Efectos de la aplicación de sustancias homeopáticas en el comportamiento agronómico y rendimiento del cultivo de nabo (Brassica napus l.). - Cervantes Molina, Jonathan Enrique (2018)
Vegetables are a fundamental source of fiber, vitamins and minerals in human nutrition. Factors such as balanced diets have increased the consumption of vegetables. In Ecuador the largest production of turnip (Brassica napus L.) occurs in the Canton Saquisilí - Province of Cotopaxi. Experiments have been carried out with herbicides and other artificially synthesized substances, applied in homeopathic form, functioning as growth promoters in plants, without producing negative effects such as the resistance of pathogenic microorganisms and damage to the environment. In relation to this, the use of agrohomeopathic substances on the germination, emergence and vegetative development of turnip plants (Brassica napus L.) was proposed. The research was carried out in the La María experimental farm in the Mocache area, located at kilometer 7.1 / 2 of the Quevedo road - El Empalme, Province of Los Ríos. For this, we used turnip plants (Brassica napus L.) that were subjected to the homeopathic substances Silicea terra, Natrum muriaticum and Phosphoric acid from the National Homeopathic Pharmacy (FHC) in Mexico, in concentrations of 6 CH and 30 CH. Germination results were obtained in which the homeopathic substances positively influenced being 7 CH of Silicea terra, 7 CH of Phosphoricum acidum and 31 CH of Natrum muriaticum the interactions that obtained the highest percentage of germination with 100% in relation that only reached the 83.5%. It was concluded that the homeopathic substances Silicea terra, Natrum muriaticum and Phosphoricum acidum exerted positive effects during the different stages of development of the turnip culture and depending on the dilutions used. Key words: Agrohomeopatía, dilutions, Hahnemann.